Sodium zirconium silicon phosphorus oxygen solid electrolyte material and its preparation method and application

By adopting the Ta-Al double substitution strategy in sodium zirconium silicon phospho-oxygen, the ionic conductivity of sodium ion solid electrolyte is improved, the problem of insufficient conductivity of existing electrolytes is solved, and a more stable crystal phase and higher conductivity is achieved.

CN116231055BActive Publication Date: 2025-04-29YIBIN NANMU NANO TECH CO LTD

Patent Information

Application Number
CN202310323386.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-29
Publication Date
2025-04-29
Estimated Expiration
2043-03-29

AI Technical Summary

Technical Problem

The existing sodium ion solid electrolytes have insufficient ionic conductivity, which limits their large-scale application in solid-state batteries.

Method used

By designing the Ta-Al double substitution strategy, Ta+ at the Zr4+ site is replaced in sodium zirconium silicon phosphooxygen, more sodium vacancies, improve the jump rate of Na+, and adjust the optimal Na+ concentration through doping of Al3+ to improve the ionic conductivity.

Benefits of technology

The ionic conductivity of sodium zirconium silicon phospho-oxygen solid electrolyte material is significantly improved, its crystal phase is stabilized, and its performance in solid-state batteries is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116231055B_ABST
    Figure CN116231055B_ABST
Patent Text Reader

Abstract

The present invention relates to a sodium zirconium silicon phosphorus oxygen solid electrolyte material, a preparation method thereof, and an application thereof. The chemical general formula of the sodium zirconium silicon phosphorus oxygen solid electrolyte material is Na 3‑x+y Zr 2‑x Ta x Si 2‑y Al y PO 12 ; wherein, the value ranges of x and y are 0.01 ≤ y ≤ x < 2, and the values of x and y satisfy the charge balance of the chemical formula. By designing a Ta-Al double substitution strategy, Ta + substitutes Zr 4+ sites in sodium zirconium silicon phosphorus oxygen, which can generate more sodium vacancies during the sintering process, thereby increasing the hopping probability of Na + , significantly changing the distribution of Na + , promoting the disordered Na + framework of the sodium zirconium silicon phosphorus oxygen solid electrolyte material, and further stabilizing its crystal phase and increasing the ionic conductivity. To prevent the reduction of the concentration of mobile Na + and the ionic conductivity caused by excessive sodium vacancies, a double substitution method of low-valent alkaline earth metal cations Al 3+ is used to adjust the optimal Na + concentration by substituting and doping inequivalent cations at the Si or Zr sites to increase the ionic conductivity. This material can be used in solid sodium ion batteries and metal sodium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a sodium zirconium silicon phosphorus oxygen solid electrolyte material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have attracted widespread attention in recent years to replace lithium-ion batteries due to their abundant and low-cost sodium resources. Similar to lithium-ion batteries, the liquid organic electrolytes currently contained in sodium-ion batteries may cause some safety issues such as leakage, flammability, and thermal instability. Exploring sodium-ion solid electrolytes as an alternative is a very ideal way to address these issues.

[0003] To date, different types of inorganic fast sodium ion solid electrolytes such as Na-β″-Al 2 O 3 , sulfide (Na 3 PS 4 、Na 2 SP 2 S 5 、Na 10 SnP 2 S 12 ), sodium superion conductor Na 1+x Zr 2 Si x P 3-x O 12 (0≤x≤3) is developed and applied to solid-state sodium ion batteries. Among them, Na-β″-Al 2 O 3 It is widely used in Na-S batteries, but Na-β″-Al 2 O 3 The high sensitivity to moisture and high sintering temperature (~1600°C) also limit their applications. Although sulfide-based solid electrolytes have high ionic conductivity and good ductility, most of them are unstable in air and show a narrow electrochemical stability window.

[0004] Compared with the above-mentioned sodium ion solid electrolytes, the sodium superion conductor Na 1+x Zr 2 Si x P 3-x O 12 It has relatively high ionic conductivity, a wide electrochemical stability window and good atmospheric stability, and has been widely studied by many scholars as a promising solid electrolyte.

[0005] Na 1+x Zr 2 Si x P 3-x O12 The synthesis was first published by Hong and Goodenough. Its octahedral structure is similar to Si / PO 4 Tetrahedrons share corner oxygen ions to form a three-dimensional framework, making sodium ion transport possible. Studies have found that at room temperature, when x = 2, Na 1+ x Zr 2 Si x P 3-x O 12 The corresponding Na 3 Zr 2 Si 2 PO 12 The ionic conductivity is the highest (~10 -4 S / cm), by doping a large amount of elements and adjusting the chemical composition at the grain boundary to increase the Na 3 Zr 2 Si 2 PO 12 Considerable efforts have been made to improve the ionic conductivity of cationic elements such as La 3+ 、Zn 2+ ,Ge 4+ , Y 3+ Mg 2+ and Nb 5+ , has been shown to assist Na 3 Zr 2 Si 2 PO 12 Solid electrolytes to improve ionic conductivity.

[0006] Sodium superion conductor Na for high-density batteries 1+x Zr 2 Si x P 3-x O 12 However, the Na 3 Zr 2 Si 2 PO 12 The ionic conductivity of solid electrolytes is still not high enough, which restricts their large-scale application in solid-state batteries. Summary of the invention

[0007] To increase Na 3 Zr 2 Si 2 PO 12 The present invention provides a sodium zirconium silicon phosphorus oxygen solid electrolyte material and a preparation method and application thereof, by designing a Ta-Al double substitution strategy. + Substituting Zr in NaZrSiP 4+sites, which can generate more sodium vacancies during the sintering process, thereby increasing the Na + The hopping probability of Na + distribution, promoting the disordered Na + framework, thereby stabilizing its crystal phase and improving ionic conductivity. In addition, to prevent excessive sodium vacancies from causing mobile Na + The concentration and ionic conductivity are reduced by using low-valent alkaline earth metal cations Al 3+ The double substitution method, in which unequal cation substitution doping at Si or Zr sites adjusts the optimal Na + concentration to increase ionic conductivity.

[0008] In the first aspect, the embodiment of the present invention provides a sodium zirconium silicon phosphorus oxygen solid electrolyte material, wherein the chemical formula of the sodium zirconium silicon phosphorus oxygen solid electrolyte material is Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 ; Among them, the value range of x and y is 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula.

[0009] In a second aspect, the present invention provides a method for preparing the sodium zirconium silicon phosphorus oxygen solid electrolyte material according to the first aspect, the preparation method comprising:

[0010] Under protective atmosphere, according to the general formula Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 , weighing the sodium source, tantalum source, silicon source, zirconium source, aluminum source and phosphorus source in a stoichiometric ratio; wherein 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula;

[0011] The weighed raw materials are ground and mixed uniformly under a protective atmosphere, and then a wet grinding medium is added to perform a first ball milling process, and the obtained first ball milling mixture is dried in a vacuum drying oven to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor;

[0012] The sodium zirconium silicon phosphorus oxygen solid electrolyte precursor is placed in a jade crucible and pre-fired to obtain a pre-fired block;

[0013] The pre-sintered block is subjected to a second ball milling process to obtain a second ball milled powder;

[0014] calcining the second ball-milled powder to perform a solid phase reaction;

[0015] After the reaction is completed, the mixture is naturally cooled to room temperature, and then a third ball milling treatment is performed to obtain the desired sodium zirconium silicon phosphorus oxygen type solid electrolyte material.

[0016] Preferably, the drying temperature is 100° C. to 200° C., and the drying time is 5 hours to 8 hours.

[0017] Preferably, the sodium source includes one or more of sodium hydroxide, sodium carbonate, sodium perchlorate, and sodium bis(trifluoromethylsulfonyl)imide;

[0018] The tantalum source includes one or more of tantalum oxide, tantalum nitrate, tantalum chloride, and tantalum fluoride;

[0019] The silicon source includes one or more of silicon dioxide and silicate;

[0020] The zirconium source includes one or more of zirconium oxide, zirconium nitrate, and zirconium acetate;

[0021] The aluminum source includes one or more of aluminum oxide and metaaluminate;

[0022] The phosphorus source is one or more of phosphorus pentoxide, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0023] Preferably, the sodium source needs to be in excess of 1% to 15% in molar ratio.

[0024] Preferably, the rotation speed of the first ball mill is 500 rpm to 800 rpm, and the time of the first ball mill is 12 hours to 15 hours;

[0025] The rotation speed of the second ball mill is 500 rpm to 800 rpm, and the time of the second ball mill is 12 hours to 15 hours;

[0026] The rotation speed of the third ball mill is 400 rpm to 600 rpm, and the time of the third ball mill is 6 hours to 8 hours.

[0027] Preferably, the pre-firing temperature is 300° C. to 400° C., the heating rate is 3° C. / min to 4° C. / min, and the pre-firing time is 15 hours to 18 hours.

[0028] Preferably, the calcination temperature is 1000° C. to 1100° C., the heating rate is 3° C. / min to 4° C. / min, and the calcination time is 5 hours to 8 hours.

[0029] Preferably, the wet grinding medium includes one or more of deionized water, ethanol, propanol, ethylene glycol, and polyvinyl alcohol.

[0030] In a third aspect, the present invention provides a sodium battery, comprising a sodium zirconium silicon phosphorus oxygen solid electrolyte material prepared by the preparation method described in the second aspect above.

[0031] The sodium zirconium silicon phosphorus oxygen solid electrolyte material provided in the embodiment of the present invention designs a Ta-Al double substitution strategy to replace Ta + Substituting Zr in NaZrSiP 4+ sites can generate more sodium vacancies during the sintering process, thereby increasing the Na + The jump rate of Na + distribution, promoting the disordered Na + framework, thereby stabilizing its crystal phase and improving ionic conductivity. In addition, to prevent excessive sodium vacancies from causing mobile Na + The concentration and ionic conductivity are reduced by using low-valent alkaline earth metal cations Al 3+ The double substitution method, in which unequal cation substitution doping at Si or Zr sites adjusts the optimal Na + concentration to increase ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0033] Figure 1 A flow chart of a method for preparing a sodium zirconium silicon phosphorus oxygen solid electrolyte material provided in an embodiment of the present invention;

[0034] Figure 2 X-ray diffraction (XRD) diagrams of the sodium zirconium silicon phosphorus oxygen solid electrolyte materials obtained in Examples 1 to 5 of the present invention and Comparative Examples 1-2 were performed. DETAILED DESCRIPTION

[0035] The present invention is further described below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0036] In order to improve the electrical conductivity, the present invention provides a sodium zirconium silicon phosphorus oxygen solid electrolyte material, the chemical formula of the sodium zirconium silicon phosphorus oxygen solid electrolyte material is Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 ; Among them, the value range of x and y is 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula.

[0037] The sodium zirconium silicon phosphorus oxygen solid electrolyte provided by the present invention is a tantalum-aluminum doped sodium zirconium silicon phosphorus oxygen solid electrolyte material. 4+ Site and Si 4+ Site tuning for optimal Na by substitutional doping with inequivalent cations + concentration, producing more sodium vacancies, thereby reducing grain boundary resistance, forming a stable crystal phase, and improving ionic conductivity. It can be used as an ideal solid electrolyte material in all-solid-state sodium-ion secondary batteries and can also be used in metal sodium batteries.

[0038] like Figure 1 As shown, the preparation method of the sodium zirconium silicon phosphorus oxygen solid electrolyte material provided by the present invention mainly comprises the following steps:

[0039] Step 110, under a protective atmosphere, according to the general formula Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 , weigh the sodium source, tantalum source, silicon source, zirconium source, aluminum source and phosphorus source in a stoichiometric ratio; wherein 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula.

[0040] In order to compensate for the volatilization loss of the sodium source during the sintering process, the sodium source needs to be in excess of 1% to 15% by molar ratio. In this step, the protective atmosphere includes but is not limited to nitrogen and argon. Preferably, x=0.4, y=0.2.

[0041] The sodium source includes one or more of sodium hydroxide, sodium carbonate, sodium perchlorate, and sodium bis(trifluoromethanesulfonyl)imide;

[0042] The tantalum source includes one or more of tantalum oxide, tantalum nitrate, tantalum chloride, and tantalum fluoride;

[0043] The silicon source includes one or more of silicon dioxide and silicate;

[0044] The zirconium source includes one or more of zirconium oxide, zirconium nitrate, and zirconium acetate;

[0045] The aluminum source includes one or more of aluminum oxide and metaaluminate;

[0046] The phosphorus source is one or more of phosphorus pentoxide, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

[0047] Step 120, grind and mix the weighed raw materials evenly under a protective atmosphere, add a wet grinding medium, perform a first ball milling treatment, and dry the obtained first ball milled mixture in a vacuum drying oven to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor.

[0048] In this step, the protective atmosphere is the same as that in step 110, including but not limited to nitrogen and argon.

[0049] The wet grinding medium includes one or more of deionized water, ethanol, propanol, ethylene glycol, and polyvinyl alcohol. To achieve a better ball milling effect, in this step, the ratio of the total mass of the wet grinding medium to the raw material is 1:0.8 to 1:1.5.

[0050] The speed of the first ball mill is 500 rpm to 800 rpm, and the time of the first ball mill is 12 hours to 15 hours. In this step, the drying temperature is 100° C. to 200° C., and the drying time is 5 hours to 8 hours.

[0051] Step 130, loading the sodium zirconium silicon phosphorus oxygen solid electrolyte precursor into a jade crucible, and pre-firing it to obtain a pre-firing block.

[0052] In this step, the pre-firing temperature is 300° C. to 400° C., the heating rate is 3° C. / min to 4° C. / min, and the pre-firing time is 15 hours to 18 hours.

[0053] Step 140, subjecting the pre-sintered block to a second ball milling process to obtain a second ball milled powder.

[0054] The rotation speed of the second ball mill is 500 rpm to 800 rpm, and the time of the second ball mill is 12 hours to 15 hours.

[0055] Step 150, calcining the second ball-milled powder to perform a solid phase reaction.

[0056] The calcination temperature is 1000° C. to 1100° C., the heating rate is 3° C. / min to 4° C. / min, and the calcination time is 5 hours to 8 hours.

[0057] Step 160, after the reaction is completed, the mixture is naturally cooled to room temperature, and then a third ball milling process is performed to obtain the desired sodium zirconium silicon phosphorus oxygen type solid electrolyte material.

[0058] The third ball milling adopts a dry milling process, the rotation speed of the third ball milling is 400 rpm to 600 rpm, and the time of the third ball milling is 6 hours to 8 hours.

[0059] The sodium zirconium silicon phosphorus oxygen solid electrolyte provided by the present invention is a tantalum-aluminum doped sodium zirconium silicon phosphorus oxygen solid electrolyte material, which is synthesized by a high temperature solid phase method. + Substituting Zr in NaZrSiP 4+ sites can generate more sodium vacancies during the sintering process, thereby increasing the Na + The jump rate of Na + distribution, promoting the disordered Na+ framework, thereby stabilizing its crystal phase and improving ionic conductivity. In addition, to prevent excessive sodium vacancies from causing mobile Na + The concentration and ionic conductivity are reduced by using low-valent alkaline earth metal cations Al 3+ The double substitution method, in which unequal cation substitution doping at Si or Zr sites adjusts the optimal Na + The sodium zirconium silicon phosphorus oxygen solid electrolyte material prepared by the above method can be used in solid sodium ion batteries and metal sodium batteries, and the preparation method is environmentally friendly, energy-saving, and suitable for large-scale production.

[0060] In order to better understand the technical solution provided by the present invention, the following uses a number of specific examples to illustrate the specific process of preparing sodium zirconium silicon phosphorus oxygen solid electrolyte material using the method provided in the above embodiment of the present invention, as well as the conductive properties.

[0061] Example 1

[0062] The general formula for preparation is Na 2.99 Zr 1.98 Ta 0.02 Si 1.99 Al 0.01 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0063] (1) Under nitrogen atmosphere, weigh sodium hydroxide (NaOH), zirconium oxide (ZrO 2 ), Tantalum Oxide (Ta 2 O 5 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), diammonium phosphate (NH 4 H 2 PO 4 ) raw materials. In order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 1% in excess by molar ratio.

[0064] (2) After the weighed raw materials are ground and mixed uniformly under a nitrogen atmosphere, deionized water is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 120° C. for 7 hours to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 600 rpm, the time is 14 hours, and the ratio of the total mass of deionized water to the raw materials is 1:0.8.

[0065] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor was placed in a corundum crucible and placed in a muffle furnace, and heated to 350° C. at a heating rate of 3.5° C. / min for pre-calcination for 16 hours to obtain a pre-calcined block.

[0066] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 700 rpm and the time is 13 hours.

[0067] (5) The obtained second ball-milled powder was heated to 1050° C. at a heating rate of 4° C. / min and calcined for 6 h to carry out a solid phase reaction.

[0068] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 2.99 Zr 1.98 Ta 0.02 Si 1.9 9 Al 0.01 PO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the third ball milling speed is 500 rpm and the time is 7 hours.

[0069] Example 2

[0070] The general formula for preparation is Na 2.8 Zr 1.6 Ta 0.4 Si 1.8 Al 0.2 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0071] (1) Under nitrogen atmosphere, weigh sodium carbonate (Na2CO3) in a molar ratio of [1.4×(1+10%)]:1.6:0.4:1.8:0.1:1. 2 CO 3 )、Zr(NO 3 ) 4 ), tantalum chloride (TaCl 5 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 ) raw materials. In order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 10% excessive in molar ratio.

[0072] (2) After the weighed raw materials are ground and mixed uniformly under a nitrogen atmosphere, ethanol is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 150° C. for 6 hours to evaporate the ethanol and obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 500 rpm, the time is 13 hours, and the ratio of the total mass of ethanol to the raw materials is 1:1.

[0073] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor was placed in a corundum crucible and placed in a muffle furnace, and heated to 350° C. at a heating rate of 3° C. / min for pre-calcination for 18 hours to obtain a pre-calcined block.

[0074] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 800 rpm and the time is 12 hours.

[0075] (5) The obtained second ball-milled powder was heated to 1100° C. at a heating rate of 4° C. / min and calcined for 7 hours to carry out a solid phase reaction.

[0076] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 2.8 Zr 1.6 Ta 0.4 Si 1.8 Al 0.2 PO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the rotation speed of the third ball mill is 600 rpm and the time is 6 hours.

[0077] Example 3

[0078] The general formula for preparation is Na 3 Zr 1.2 Ta 0.8 Si 1.2 Al 0.8 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0079] (1) Under argon atmosphere, weigh sodium perchlorate (NaClO) in a molar ratio of [3×(1+8%)]:1.2:0.8:1.2:0.4:0.5. 4 )、Zr(NO 3 ) 4 ), tantalum fluoride (TaF 5 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), phosphorus pentoxide (P 2 O 5) raw materials. In order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 8% in excess by molar ratio.

[0080] (2) After the weighed raw materials are ground and mixed uniformly under an argon atmosphere, propanol is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 200° C. for 5 hours to evaporate the propanol and obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 700 rpm, the time is 12 hours, and the ratio of the total mass of propanol to the raw materials is 1:1.3.

[0081] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor is loaded into a corundum crucible and placed in a muffle furnace, and heated to 400° C. at a heating rate of 4° C. / min for pre-calcination for 15 hours to obtain a pre-calcined block.

[0082] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 600 rpm and the time is 14 hours.

[0083] (5) The obtained second ball-milled powder was heated to 1100° C. at a heating rate of 3.5° C. / min and calcined for 5 hours to carry out a solid phase reaction.

[0084] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 3 Zr 1.2 Ta 0.8 Si 1.2 Al 0.8 PO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the rotation speed of the third ball mill is 600 rpm and the time is 7 hours.

[0085] Example 4

[0086] The general formula for preparation is Na 2.5 Zr 0.5 Ta 1.5 SiAlPO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0087] (1) Under nitrogen atmosphere, weigh sodium hydroxide (NaOH), zirconium acetate (Zr(CH 3 COO 4 ), tantalum chloride (TaCl 5 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), phosphorus pentoxide (P 2 O5 ) raw materials. In order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 5% in excess by molar ratio.

[0088] (2) After the weighed raw materials are ground and mixed uniformly under a nitrogen atmosphere, polyvinyl alcohol is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 100° C. for 8 hours to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 800 rpm, the time is 13 hours, and the ratio of the total mass of polyvinyl alcohol to the raw materials is 1:1.4.

[0089] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor was loaded into a corundum crucible and placed in a muffle furnace, and heated to 300° C. at a heating rate of 4° C. / min for pre-calcination for 17 hours to obtain a pre-calcined block.

[0090] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 550 rpm and the time is 15 hours.

[0091] (5) The obtained second ball-milled powder was heated to 1000° C. at a heating rate of 3° C. / min and calcined for 6 hours to carry out a solid phase reaction.

[0092] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 2.5 Zr 0.5 Ta 1.5 SiAlPO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the third ball milling speed is 400 rpm and the time is 8 hours.

[0093] Example 5

[0094] The general formula for preparation is Na 2.7 Zr 0.1 Ta 1.9 Si 0.4 Al 1.6 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0095] (1) Under argon atmosphere, weigh sodium bis(trifluoromethylsulfonyl)imide (C) in a molar ratio of [2.7×(1+15%)]:0.1:1.9:0.4:0.8:0.5. 2 F 6 NNaO 4 S 2 )、ZrO 2 ), Tantalum nitrate (Ta(NO 3 ) 5 ), silicon dioxide (SiO2 ), aluminum oxide (Al 2 O 3 ), phosphorus pentoxide (P 2 O 5 ) raw materials. In order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 15% excessive in molar ratio.

[0096] (2) After the weighed raw materials are ground and mixed uniformly under an argon atmosphere, ethylene glycol is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 180° C. for 5.5 hours to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 650 rpm, the time is 15 hours, and the ratio of the total mass of ethylene glycol to the raw materials is 1:1.5.

[0097] (3) placing the obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor into a corundum crucible and placing it in a muffle furnace, heating it to 350° C. at a heating rate of 3° C. / min for pre-calcining for 16 hours to obtain a pre-calcined block;

[0098] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 500 rpm and the time is 14 hours.

[0099] (5) The obtained second ball-milled powder was heated to 1050° C. at a heating rate of 4° C. / min and calcined for 6 hours to carry out a solid phase reaction.

[0100] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 2.7 Zr 0.1 Ta 1.9 Si 0.4 Al 1.6 PO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the third ball milling speed is 550 rpm and the time is 7 hours.

[0101] Comparative Example 1

[0102] Comparative Example 1 Compared with Example 1, only tantalum doping was performed without aluminum doping, and a general formula of Na 2.6 Zr 1.6 Ta 0.4 Si 2 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0103] (1) Under nitrogen atmosphere, weigh sodium hydroxide (NaOH), zirconium oxide (ZrO 2 ), Tantalum Oxide (Ta2 O 5 ), silicon dioxide (SiO 2 ), diammonium phosphate (NH 4 H 2 PO 4 ) raw materials, wherein, in order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 1% in excess on a molar basis.

[0104] (2) After the weighed raw materials are ground and mixed uniformly under a nitrogen atmosphere, deionized water is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 120° C. for 7 hours to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 600 rpm, the time is 14 hours, and the ratio of the total mass of deionized water to the raw materials is 1:0.8.

[0105] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor was placed in a corundum crucible and placed in a muffle furnace, and heated to 350° C. at a heating rate of 3.5° C. / min for pre-calcination for 16 hours to obtain a pre-calcined block.

[0106] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 700 rpm and the time is 13 hours.

[0107] (5) The obtained second ball-milled powder was heated to 1050° C. at a heating rate of 4° C. / min and calcined for 6 h to carry out a solid phase reaction.

[0108] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 2.6 Zr 1.6 Ta 0.4 SiPO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, wherein the third ball milling speed is 500 rpm and the time is 7 hours.

[0109] Comparative Example 2

[0110] Comparative Example 2 Compared with Example 1, no tantalum-aluminum doping was performed, and a general formula of Na 3 Zr 2 Si 2 PO 12 Sodium zirconium silicon phosphorus oxygen solid electrolyte material.

[0111] (1) Under nitrogen atmosphere, weigh sodium hydroxide (NaOH), zirconium oxide (ZrO 2 ), silicon dioxide (SiO 2 ), diammonium phosphate (NH 4 H2 PO 4 ) raw materials; wherein, in order to compensate for the volatilization loss of the sodium source in the subsequent sintering process, the amount of the sodium source needs to be 1% in excess by molar ratio.

[0112] (2) After the weighed raw materials are ground and mixed uniformly under a nitrogen atmosphere, deionized water is added and the first ball milling is performed. The first ball milling mixture is dried in a vacuum drying oven at 120° C. for 7 hours to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; wherein the first ball milling speed is 600 rpm, the time is 14 hours, and the ratio of the total mass of deionized water to the raw materials is 1:0.8.

[0113] (3) The obtained sodium zirconium silicon phosphorus oxygen solid electrolyte precursor was placed in a corundum crucible and placed in a muffle furnace, and heated to 350° C. at a heating rate of 3.5° C. / min for pre-calcination for 16 hours to obtain a pre-calcined block.

[0114] (4) subjecting the obtained pre-sintered block to a second ball milling treatment to obtain a second ball milled powder; wherein the second ball milling speed is 700 rpm and the time is 13 hours.

[0115] (5) The obtained second ball-milled powder was heated to 1050° C. at a heating rate of 4° C. / min and calcined for 6 h to carry out a solid phase reaction.

[0116] (6) After the reaction, the mixture was naturally cooled to room temperature and subjected to a third ball milling to obtain a composition of Na 3 Zr 2 Si 2 PO 12 The sodium zirconium silicon phosphorus oxygen type solid electrolyte material, the third ball milling speed is 500 rpm, and the time is 7 hours.

[0117] X-ray diffraction analysis was performed on the sodium zirconium silicon phosphorus oxygen type solid electrolyte materials prepared in Examples 1-5 and Comparative Examples 1-2. 3 Zr 2 Si 2 PO 12 For a standard card, the result is Figure 2 As shown. Examples 1-5 and Comparative Examples 1-2 correspond to sodium zirconium silicon phosphorus oxygen type solid electrolyte materials prepared when x=0.02, y=0.01, x=0.4, y=0.2, x=0.8, y=0.8, x=1.5, y=1, x=1.9, y=1.6, x=0.4, y=0 and x=0, y=0, respectively. Figure 2 It can be seen that the XRD spectra of the sodium zirconium silicon phosphorus oxygen type solid electrolyte materials prepared in Examples 1-5 and Comparative Examples 1-2 are consistent with the standard Cartesian diffraction peaks, and no impure phases are produced, indicating that neither tantalum doping nor tantalum-aluminum co-doping affects the diffraction peaks and no impurity phases are produced.

[0118] The powder conductivity of the sodium zirconium silicon phosphorus oxygen type solid electrolyte material prepared in Example 1-5 and Comparative Example 1-2 was tested using a ROOKO tester. The test results are shown in Table 1.

[0119] project Ionic conductivity S / cm Example 1 <![CDATA[5.86×10 -4 ]]> Example 2 <![CDATA[7.98×10 -4 ]]> Example 3 <![CDATA[6.32×10 -4 ]]> Example 4 <![CDATA[6.73×10 -4 ]]> Example 5 <![CDATA[6.48×10 -4 ]]> Comparative Example 1 <![CDATA[3.72×10 -4 ]]> Comparative Example 2 <![CDATA[2.24×10 -4 ]]>

[0120] Table 1

[0121] It can be seen from Table 1 that the ionic conductivity of the material in Comparative Example 2 is the lowest, the ionic conductivity of the material in Comparative Example 1 is the second, and the ionic conductivity of the materials in Examples 1-5 is significantly increased, among which the ionic conductivity of the material in Example 2 reaches 7.98×10 -4 S / cm, which shows that the ionic conductivity of the sodium zirconium silicon phosphorus oxygen type solid electrolyte material without any doping is the lowest, and the ionic conductivity of the tantalum-doped material is significantly increased, but it is significantly lower than the ionic conductivity of the tantalum-aluminum co-doped material. This is because Ta + Substituting Zr in NaZrSiP 4+ sites can generate more sodium vacancies during the sintering process, thereby increasing the Na + The jump rate of Na + distribution, promoting the disordered Na + The aluminum doping can prevent the excessive sodium vacancies from causing the mobile Na + concentration and ionic conductivity, substitutional doping of unequal cations at Si or Zr sites can tune the optimal Na + The concentration is increased to improve the ionic conductivity. That is, the ionic conductivity is improved because the present invention generates more sodium vacancies through tantalum-aluminum unequal co-doping, and at the same time reduces the grain boundary resistance, which is conducive to stabilizing the cubic phase and improving the ionic conductivity.

[0122] In summary, the present invention is to solid electrolyte Na 3 Zr 2 Si 2 PO 12 Double ion doping modification is carried out to improve the ionic conductivity and provide a solid electrolyte material with good performance and simple preparation.

[0123] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A sodium zirconium silicon phosphorus oxygen solid electrolyte material, characterized in that: The general chemical formula of the sodium zirconium silicon phosphorus oxygen solid electrolyte material is Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 ; Among them, the value range of x and y is 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula.

2. A method for preparing the sodium zirconium silicon phosphorus oxygen solid electrolyte material according to claim 1, characterized in that: The preparation method comprises: Under protective atmosphere, according to the general formula Na 3-x+y Zr 2-x Ta x Si 2-y Al y PO 12 , weighing the sodium source, tantalum source, silicon source, zirconium source, aluminum source and phosphorus source in a stoichiometric ratio; wherein 0.01≤y≤x<2, and the values ​​of x and y satisfy the charge balance of the chemical formula; The weighed raw materials are ground and mixed uniformly under a protective atmosphere, and then a wet grinding medium is added to perform a first ball milling process, and the obtained first ball milling mixture is dried in a vacuum drying oven to obtain a sodium zirconium silicon phosphorus oxygen solid electrolyte precursor; The sodium zirconium silicon phosphorus oxygen solid electrolyte precursor is placed in a jade crucible and pre-fired to obtain a pre-fired block; The pre-sintered block is subjected to a second ball milling process to obtain a second ball milled powder; calcining the second ball-milled powder to perform a solid phase reaction; After the reaction is completed, the mixture is naturally cooled to room temperature, and then a third ball milling treatment is performed to obtain the desired sodium zirconium silicon phosphorus oxygen type solid electrolyte material.

3. The preparation method according to claim 2, characterized in that: The drying temperature is 100°C to 200°C, and the drying time is 5 hours to 8 hours.

4. The preparation method according to claim 2, characterized in that: The sodium source includes one or more of sodium hydroxide, sodium carbonate, sodium perchlorate, and sodium bis(trifluoromethylsulfonyl)imide; The tantalum source includes one or more of tantalum oxide, tantalum nitrate, tantalum chloride, and tantalum fluoride; The silicon source includes one or more of silicon dioxide and silicate; The zirconium source includes one or more of zirconium oxide, zirconium nitrate, and zirconium acetate; The aluminum source includes one or more of aluminum oxide and metaaluminate; The phosphorus source is one or more of phosphorus pentoxide, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.

5. The preparation method according to claim 2, characterized in that: In terms of molar ratio, the sodium source needs to be in excess of 1% to 15%.

6. The preparation method according to claim 2, characterized in that: The rotation speed of the first ball mill is 500 rpm to 800 rpm, and the time of the first ball mill is 12 hours to 15 hours; The rotation speed of the second ball mill is 500 rpm to 800 rpm, and the time of the second ball mill is 12 hours to 15 hours; The rotation speed of the third ball mill is 400 rpm to 600 rpm, and the time of the third ball mill is 6 hours to 8 hours.

7. The preparation method according to claim 2, characterized in that: The pre-firing temperature is 300° C. to 400° C., the heating rate is 3° C. / min to 4° C. / min, and the pre-firing time is 15 hours to 18 hours.

8. The preparation method according to claim 2, characterized in that: The calcination temperature is 1000-1100° C., the heating rate is 3° C. / min-4° C. / min, and the calcination time is 5 hours-8 hours.

9. The preparation method according to claim 2, characterized in that: The wet grinding medium includes one or more of deionized water, ethanol, propanol, ethylene glycol, and polyvinyl alcohol.

10. A sodium battery, characterized in that: The sodium battery comprises a sodium zirconium silicon phosphorus oxygen solid electrolyte material prepared by the preparation method described in any one of claims 2 to 9 above.

Citation Information

Patent Citations

  • High Conductivity NASICON Electrolyte for Room Temperature Solid-State Sodium Ion Batteries

    US20150249262A1

  • Solid electrolyte, all solid state battery, method for producing solid electrolyte, and method for producing all solid state battery

    US20190067736A1

Cited By

  • Core-shell composite material as well as preparation method and application thereof

    CN117525551A

  • A core-shell composite material, a preparation method and application thereof

    CN117525551B